2021
DOI: 10.1186/s12913-021-07007-w
|View full text |Cite
|
Sign up to set email alerts
|

A decade of commitment to hospital quality of care: overview of and perceptions on multicomponent quality improvement policies involving accreditation, public reporting, inspection and pay-for-performance

Abstract: Background Quality improvement (QI) initiatives such as accreditation, public reporting, inspection and pay-for-performance are increasingly being implemented globally. In Flanders, Belgium, a government policy for acute-care hospitals incorporates aforementioned initiatives. Currently, questions are raised on the sustainability of the present policy. Objective First, to summarise the various initiatives hospitals have adopted under government enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Since 2016, acute-care hospitals in Flanders demonstrated increased effort into these triad components. 12 However, a recent review has shown the lack of evidence for all three 'Quality-of-Care-Triad' components. 13 Furthermore, hospitals and healthcare stakeholders are critical about the sustainability of today's quality policies and voices are rising worldwide for a new approach for future quality of care initiatives.…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2016, acute-care hospitals in Flanders demonstrated increased effort into these triad components. 12 However, a recent review has shown the lack of evidence for all three 'Quality-of-Care-Triad' components. 13 Furthermore, hospitals and healthcare stakeholders are critical about the sustainability of today's quality policies and voices are rising worldwide for a new approach for future quality of care initiatives.…”
Section: Highlightsmentioning
confidence: 99%
“…This agreement introduced a ‘Quality‐of‐Care Triad’ consisting of three main components: voluntary hospital‐wide accreditation by an international external agency, voluntary measurement and public reporting of quality indicators as well as mandatory inspection by the government with an announced and unannounced part. Since 2016, acute‐care hospitals in Flanders demonstrated increased effort into these triad components 12 . However, a recent review has shown the lack of evidence for all three ‘Quality‐of‐Care‐Triad’ components 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare organisations worldwide have been initiating quality improvements and building a foundation for quality by applying many theories, methodologies and interventions [ 5 , 6 ]. In Flanders, Belgium, accreditation, public reporting and governmental inspection have been the main pillars for the development of hospital’s quality management system [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009, the government of Flanders (a 6-million population region in Belgium) based its hospital quality of care policy on a triad consisting of voluntary accreditation by an external agency, mandatory inspection by the Flemish authorities and voluntary public reporting of quality indicators [8]. Almost all (98%) Flemish hospitals have obtained an accreditation label from JCI or Qualicor by now.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all (98%) Flemish hospitals have obtained an accreditation label from JCI or Qualicor by now. The decision for accreditation is made by the hospitals and all associated costs are paid by them, with limited governmental financial support [8]. When successful, the hospital is granted a quality label valid for a defined period in time, after which it can apply for accreditation renewal.…”
Section: Introductionmentioning
confidence: 99%